Anda di halaman 1dari 7

6.

dx

6+10 sin x

x
sin


1t 2
dt
2
1+t

2t
6+10
1+ t 2

( )

( )

1t 2
dt
2
1+ t

( )

6+6 t 2 +20 t
1+t 2
2

1t
2
6+ 6 t +20 t

1t 2
dt
6 t 2 +20 t+6

1t 2
6 t 220 t+ 6

1t 2

2 ( 3 t 210 t+3 t )
2

1
1t
2 3 t 210 t+3

1
1t
dt

2 ( t3 ) ( 3 tt )

( 1t ) ( 1+t )
1
dt

2 ( t3 ) ( 3 t1 )

1
A
B
+

2 ( t3 ) (3 t 1 )

1 A ( 3 t1 )+ B ( t3 )
( t3 ) ( 3 t1 )
2

1 A 3 t A + Bt3 B
( t 3 )( 3 t 1 )
2

1 ( 3 A+ B ) tA3 B
( t3 ) (3 t1 )
2

3 A +B = -1
A 3B = 1

1
3

= 3A + B = -1
= 3A 9B = 3
10B = -4
B
= -4
10
B

3 a+

(25 )=1

3 A=1+

3 A=

2
5

7
5

7 1 7
A= . =
5 3 15

= -2
5

1
A
B
+
dt

2 ( t3 ) (3 t1)

7
1
15 1 2

+ .
2 ( t3 ) 2 5

dt
( ) (3 t1)

1 7
dt 1 2
.
+ .
ln 3 t1+ c
2 15 t3 2 10

( )

7
1
2
1
ln tg x3+
ln3 tg x 1+ c
30
2
10
3

7
1
2
1
tg x3 ln tg x1+ c
30
2
10
3

( )

7. ) cos
(

4 dx
4
x +sin x

4 dx
cos x +sin x ) ( cos 2 x +sin2 x )
2

4 dx
( 1 ) ( 1 )2 sin 2 x cos 2 x

4
12sin 2 x cos2 x

4 dx
cos 2 xcos 2 x +1

dx

4 dx
( 2 cos x1 ) cos 2 x +1

4 dx
2
cos x

dx
cos 2 x

4 tg x+ C

2 x 2 4 x 2
( x 1)( x 2) dx
9.

2 x 2 4 x 2
( x 1)( x 2)
=

A
B
C

( x 1) ( x 2) ( x 2) 2

A( x 2) 2 B ( x 1)( x 2) C ( x 1)

( x 1)( x 2) 2
Ax 2 4 Ax 4 A Bx 2 3Bx 2 B Cx C )

( x 1)( x 2) 2

( A B ) x 2 (4 A 3B C ) x 4 A 2 B C
( x 1)( x 2) 2

* A B 2...................(1)
*4 A 3B C 4.........(2)
*4 A 2 B C 2............(3)
Dari persamaan (2) dan (3) :
4 A 3B C 4
4 A 2B C 2

B = -6

Dari persamaan (1) A + B = -2


A + (-6) = -2
A= 4
A

( x 1) ( x 2) ( x 2)

* Dari persamaan (2)


4A + 3B + C = -4
4(4) + 3(-6) + C = -4
16 18 + C = -4
C = -2

dx

4
6
2

dx
( x 1) ( x 2) ( x 2) 2

d ( x 1)
d ( x 2)
dx 6
dx 2 ( x 2) 2 d ( x 2)
( x 1)
( x 2)

( x 2) 1
C
1
2
4 ln( x 1) 6 ln( x 2)
C
( x 2)
4 ln( x 1) 6 ln( x 2) 2

4 sin x

10.

4cos 2 x dx

2t
2
1+t
4
2
1t
4
1+t 2

2 dt
1+t 2

( )

2t
1+t 2

2 dt
2
4 ( 1+t )( 1t ) 1+ t
2 2

( 1+t 2 )
t dt

16

2 2

4 ( 1+t ) ( 1t )

16

t dt
4
2
3t +4t

16

dt
3t +4t

16

( At + 3Btt +C+ 4 ) dt

16

16

1 3
t
4
4
+
dt
t 3 t 2+ 4

1 3
t
4
4
+
dt
t 3 t 2+ 4

16

1 dt 3 1

4 t 4 6

16

1
3 1
ln t
ln ( 3 t 2+ 4 ) +C
4
4 6

d ( 3 t2 + 4 )
2
( 3 t +4 )

()

()

4 ln t2 ln ( 3 t 2+ 4 ) +C

1
1
4 ln tan x 2 ln 3 tan 2 x +4 +C
2
2